The Role of Vacuum-Assisted Wound Closure Therapy after the Surgical Treatment of the Pilonodal Sinus - M. F. Cherkasov; K. M. Galashokyan; Yu. M. Startsev; D. M. Cherkasov; A. A. Pomazkov; S. G. Melikova; V. Yu. Katsiyaev; A. A. Matvienko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. This study is aimed at improving the treatment of patients with the pilonidal sinus (PS) by open wound healing methods.Materials and methods. The study included 54 patients with PS. The main group consisted of 29 patients treated by an open (exposure) management technique and a subsequent vacuum-assisted wound closure therapy. The control group consisted of 25 patients treated with conventional ointment bandages.Results. On the 8th day of vacuum-assisted therapy (VAC-therapy), the areas of granulation tissue were identified in 23 (79.3 %) and 10 (40.0 %) (p = 0.041) cases in the main group and the control group, respectively. Following one month of treatment, complete wound healing was observed in 24 (82.8 %) patients in the main group, with no patients in the control group showing signs of complete healing (p < 0.0001). Cytologically, starting from the 8th day of VAC-therapy, a decrease in inflammation was observed in 24 (82.8 %) patients in the main group, with the wound regenerative processes being recorded on the 16th day in 17 (58.6 %) patients (p < 0.05). The average rate of wound healing in the main group was significantly higher and equal to 2.15 ± 0.15 cm2/day, compared to the value of 0.76 ±0.18 cm2/day in the control group.Conclusion. Vacuum-assisted wound closure therapy is an effective way to stimulate reparative processes during the open management of wounds after the surgical treatment of PS. Aim. This study is aimed at improving the treatment of patients with the pilonidal sinus (PS) by open wound healing methods.Materials and methods. The study included 54 patients with PS. The main group consisted of 29 patients treated by an open (exposure) management technique and a subsequent vacuum-assisted wound closure therapy. The control group consisted of 25 patients treated with conventional ointment bandages.Results. On the 8th day of vacuum-assisted therapy (VAC-therapy), the areas of granulation tissue were identified in 23 (79.3 %) and 10 (40.0 %) (p = 0.041) cases in the main group and the control group, respectively. Following one month of treatment, complete wound healing was observed in 24 (82.8 %) patients in the main group, with no patients in the control group showing signs of complete healing (p < 0.0001). Cytologically, starting from the 8th day of VAC-therapy, a decrease in inflammation was observed in 24 (82.8 %) patients in the main group, with the wound regenerative processes being recorded on the 16th day in 17 (58.6 %) patients (p < 0.05). The average rate of wound healing in the main group was significantly higher and equal to 2.15 ± 0.15 cm2/day, compared to the value of 0.76 ±0.18 cm2/day in the control group.Conclusion. Vacuum-assisted wound closure therapy is an effective way to stimulate reparative processes during the open management of wounds after the surgical treatment of PS.